Anaerobic Baffled Reactor with Unequal Length Chambers Treating Domestic Sewage - Song, Tie-Hong; Gao, Yan-Jiao (Asian Journal of Chemistry, 2013)
In this paper, the anaerobic baffled reactor with unequal length chambers was used to treat domestic sewage. Several influence factors such as temperature, hydraulic retention time, organic load, pH, volatile fatty acid and effulent alkalinity were tested to discuss characteristics of the anaerobic baffled reactor. The results showed that the optimal operation temperature of anaerobic bacteria in this system was 30 ºC, The optimum hydraulic retention time was 6 h and pH, volatile fatty acid were also important factors for treating efficiecncy. During 2-months operation, the removal rate of COD is more stable, basiclly 80 % above which attributed to mode of unequal length chambers.